Role of Celebrity Endorser on Brand Credibility, Loyalty, and Commitment on Mobile Banking Users - Altaviar Alam Firdaus; Rizky Luxianto (Publikasi Indonesia, 2024)
This study aims to examine how celebrity credibility affects brand credibility and how it develops trust, loyalty, and long-term commitment among mobile banking customers. The proposed model was empirically evaluated using survey data from 201 mobile banking users in Indonesia who knew who their endorser bank was. In addition, SEM PLS was used to investigate the relationship between the research model's constructs. Brand credibility mediates the positive effect of celebrity credibility on mobile banking celebrity endorsement in Indonesia. In this study, the researcher focuses on the specific banking product, “Mobile Banking,” and examines the relationship between celebrity credibility, brand credibility, loyalty, and commitment. Practical/Policy implication: This study will give the company a clear view of efficiently selecting the right endorser for mobile banking in Indonesia.